Influences of vehicle to grid (V2G) on power grid: An analysis by considering associated stochastic parameters explicitly - TEKİNER MOĞULKOÇ, HATİCE (ELSEVIER, 2021)
Integration of the electric vehicles (EVs) and vehicle-to-grid (V2G) technology with renewable energy sources (RESs) is the hottest topics among researchers. Many studies have been done in this field, but in most of them, discussion of aspects of electrified transportation have been limited. The V2G system due to its structure and supporting role for the grid influences the power demand and supply curve simultaneously depending on the patterns of driving, preferences for charging/discharging times, location, and the infrastructure of the system. Due to complexity of this system, it is necessary to cover all the influential elements in one package and analyze the impact of the system on them in a unique process. In this paper, we apply a precise and efficient methodology to analyze the impacts of the EVs and V2G on reliability, cost, and emissions with respect to the power grid. The strength of this paper is the applicability of the suggested methodology to the power grids with different patterns and features with respect to shares of RESs generated power by explicitly considering the stochastic parameters shaping the daily demand/supply curves. We introduce two novel indexes for measuring the reliability of the power grid based on availability of the RESs under power supply systems: stochastic and constant power supply. To cover all the possibilities, based on different penetration levels of EVs and V2G, charging modes, locations and schedules several cases are defined and for each case, the Monte Carlo simulation is used to evaluate the impacts of the considered cases regarding the reliability, emission, and cost of the power grid. In the numerical analysis under assumed cases, results show integration of the EVs and V2G system in stochastic power supply (high RESs) improves the power grid's efficiency in terms of decreasing the total cost and emission rate. The intermittent nature of RESs can increase fluctuation in the power grid and consequently negatively affect the reliability of the system but our analysis indicates that integration of these sources with V2G system can improve the reliability of the power grid. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: Electric vehicle (EV); Vehicle to grid (V2G); Monte Carlo simulation; Reliability; Emission; Cost; Power Grid; ELECTRIC VEHICLES; MANAGEMENT; SYSTEMS; GAS; TECHNOLOGY; REDUCTION; STRATEGY; IMPACT